Principle of Powers problem

Hi, first post:

I'm helping a student work a radical equation and have a question. Here is the problem:

√2X-5 = 1 + √X - 3 (2X - 5 AND X - 3 ARE ALL UNDER THE RADICAL SIGN)

Step 2: (√2x – 5)2 = (1 + √x-3)2

Step 3: 2x – 5 = 1 = 2√x-3 + (x -3 ) à My question is HOW did they get the 2 in front of the radical sign!!!

Step 4: x – 3 = 2√x-3 à so I’m really lost on this one.

The answer is x = 7 or x = 3 but WHAT did they do between step 2 and step 3 to get the 2 in front of the radical sign?

Thanks.